From Anthropocentrism to Care for Our Common Home: Ethical Response to the Environmental Crisis - Y. I. Muliarchuk (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose of the study is explication of ethical and existential conditions of realization of human responsibility for the protection and recreation of the environment on a scale of the common world with all the other living beings. The crisis of the environment is the crisis of human morality. For responsible environmental management, it is necessary to form the ecological consciousness of society and reinterpret the anthropocentrism on the ethical foundations. The theoretical basis of the research is the analysis of ethical and existential dimensions of understanding of the human environment ranging from the sphere of the home and the natural environment to the dimension of the common world of people and all the entities. The work clarifies the genesis of the concept of home from the ancient "oikos", household to the idea of home as a "hub", a base for mental and physical mobility in the contemporary technosphere. Correspondent to the transformation of the living world of mankind is the concept of communication and universal discourse of norms and values of human coexistence of J. Habermas, К.-О. Apel, D. Böhler, W. Kuhlmann, and others. The domain of the ecological consciousness and behaviour also requires motivation at the level of human feelings, beliefs, and convictions, which is represented by the philosophic and religious thought of H. Jonas, O. Leopold, K. M. Меуеr-Abich, A. Naess, the pope Francis, and others. As the result, the study proves the relevance of the concept of care about the common home based on the recognition of the value of the existence of all beings. Originality. The study explicates the genesis and meaning of the ethos of the common home with values of love, care, openness, solidarity, freedom, and responsibility which is proved to be the ethical and existential condition of the solution of the environmental crisis. The traditional anthropocentrism is reinterpreted towards the duty of people to be the centre of the responsibility for the existence of all beings that requires both reason and care. Conclusions. The ethics of care for our common home completes the moral duty of people as providers of the universal discourse who represent the interests of all beings. Concern for the preservation of the human environment and of all creation makes it possible for humanity to realize its universal responsibility in the world. The contemporaneous science and religious thought modify anthropocentrism to the holistic ethical understanding of human’s mission to be responsible for all beings.